Infrastructure Asset Management Study At PDAM Tanah Laut Regency Risk-Based - Yulian, Irfani; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The performance audit by the Badan Pengawasan Keuangan dan Pembangunan (BPKP) in 2020 resulted in several evaluations that must be carried out immediately by the PDAM Tanah Laut regency, one of which is the absence of asset management policies that have not considered the risk of asset operational failure. The rate of water leakage (non revenue water) was found to be still higher than the standard of 25% at 32.01%. The high nrw is certainly related to the company's critical assets, namely network pipes and physical assets. In addition, mitigation is needed on the management of assets that have the potential to occur risks. This study aims to identify potential risks, identify potential risks, identify and determine dominant risks and provide risk mitigation recommendations on PDAM infrastructure assets in Tanah Laut Regency. Risk analysis uses probability impact matrix (PIM) risk assessment and Pareto diagram. This study resulted in a respondent's perception of 59.17% with a total of 32 potential risk variables, consisting of 9 risks in the raw water unit category, 9 risks in the production unit category, 10 risks in the distribution unit category and 4 risks in the service unit category. . Meanwhile, from the analysis that has been carried out, it is obtained that the dominant risk variables that occur in PDAM Tanah Laut assets using both the PIM method and the Pareto diagram are river water receding due to the dry season, leaks in distribution pipes, and power outages from PLN during peak hours. The mitigation strategy is for risks due to receding river water due to the dry season by increasing reservoir capacity and increasing the construction of ponds and reservoirs around the WTP buildings. For risks due to leaks in distribution pipes by providing spare pipes, replacing pipes periodically with better specifications and implementing SOPs related to pipe installation and accessories better. And for risks due to power outages from PLN during peak hours for providing Generator Sets (Gensets), ensure sufficient fuel stocks and coordinate with PLN to find out and obtain blackout schedules. The results of this study are expected to become a reference design for risk-based asset management for PDAM Tanah Laut Regency and handling/controlling risks in asset management to reduce potential losses suffered.